Lagrangian‐based Simulations of Hypervelocity Impact Experiments on Mars Regolith Proxy. Issue 13 (6th July 2020) - Froment, M.; Rougier, E.; Larmat, C.; Lei, Z.; Euser, B.; Kedar, S.; Richardson, J. E.; Kawamura, T.; Lognonné, P.
Abstract: Most of the surface of Mars is covered with unconsolidated rocky material, known as regolith. High‐fidelity models of the dynamics of impacts in such material are needed to help with the interpretation of seismic signals that are now recorded by SEIS, the seismometer of InSight. We developed a numerical model for impacts on regolith, using the novel Hybrid Optimization Software Suite (HOSS), which is a Lagrangian code mixing finite and discrete element formulations. We use data from hypervelocity impact experiments performed on pumice sand at the NASA Ames Vertical Gun Range to identify and calibrate key model parameters. The model provides insight into the plastic‐elastic transition observed in the data and it also demonstrates that gravity plays a key role in the material response. Waveforms for receivers situated vertically below the impact point are correctly modeled, while more research is needed to explain the shallow receivers' signals. Plain Language Summary: The generation of seismic waves by meteorite impacts in unconsolidated materials, such as Mars regolith, is a complex dynamic process. We present a numerical model based on a novel method and show its potential to explain the main characteristics of shock and seismic waves generated by impacts at laboratory scales. Our goal is to use this model to help with the analysis of data recorded during the InSight mission. Key Points: We conduct a parametric study of a novel Lagrangian numerical model of shock waves in granular media, with application to Mars regolith We validate this model with a laboratory experiment in pumice sand with an impact velocity of 0.98 km/s Amplitude of shock waves and transition to different regimes is explained by the model for the sensors placed vertically from the impact